APERFEIÇOAMENTO DE PROFESSORES DE FÍSICA E MATEMÁTICA UTILIZANDO A MODELAGEM MATEMÁTICA - Albé, Maristela de Quadros; Jung, Maria Eliani de Oliveira; Rogrigues, Ronaldo do Espirito Santo; Filippsen, Rosane Maria Jardim; Romeiro, Solange Bianco Borges (Revista Liberato, 2013)
The teachers from UNISINOS-SL and Fundação Liberato checked students´dificulties in the subjects of Math and Physics during High School, so they decided to made a proposal for a special course for updating and improvement for Math and Physics teachers who teach in this region. The course occurred with theoric and pratical classes with 180 hours, where 25 teachers/students from 15 schools was taught and developed projects about intallation of Math and Physics labs. The course offered to the teachers a method which they got an improvemet in Math model giving them instrumens and capaciting them to develop teachings strategys whose goal is to improve students´learining in those subjects.